2015
DOI: 10.1186/s12870-015-0414-8
|View full text |Cite
|
Sign up to set email alerts
|

Histone chaperones in Arabidopsis and rice: genome-wide identification, phylogeny, architecture and transcriptional regulation

Abstract: BackgroundHistone chaperones modulate chromatin architecture and hence play a pivotal role in epigenetic regulation of gene expression. In contrast to their animal and yeast counterparts, not much is known about plant histone chaperones. To gain insights into their functions in plants, we sought to identify histone chaperones from two model plant species and investigated their phylogeny, domain architecture and transcriptional profiles to establish correlation between their expression patterns and potential ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 79 publications
1
44
0
Order By: Relevance
“…However, there is a paucity of reports elucidating the role of plant histone chaperones in stress response and adaptation. Previously, through expression profiling of histone chaperones from rice and Arabidopsis, we had shown that a few putative histone chaperones show differential expression under various abiotic stress conditions (Tripathi et al, 2015). Out of the eight stress-regulated putative histone chaperones in rice, except the NAP family of proteins, all others are known to execute histone chaperone function as multimeric complexes formed by two or more polypeptides (De Koning et al, 2007;Tripathi et al, 2015); hence, altering the expression of a single member of such complexes might not show a phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there is a paucity of reports elucidating the role of plant histone chaperones in stress response and adaptation. Previously, through expression profiling of histone chaperones from rice and Arabidopsis, we had shown that a few putative histone chaperones show differential expression under various abiotic stress conditions (Tripathi et al, 2015). Out of the eight stress-regulated putative histone chaperones in rice, except the NAP family of proteins, all others are known to execute histone chaperone function as multimeric complexes formed by two or more polypeptides (De Koning et al, 2007;Tripathi et al, 2015); hence, altering the expression of a single member of such complexes might not show a phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The NAP family is generally considered to comprise H2A-H2B histone chaperones (De Koning et al, 2007). In our previous study, the phylogenetic analysis of NAP family proteins from yeast, humans, Arabidopsis (Arabidopsis thaliana), and rice showed that OsNAPL6 is evolutionarily closer to HsSET than to other NAP proteins from yeast and humans (Tripathi et al, 2015). HsSET, in spite of being a NAP family histone chaperone, is much different from other NAP family proteins showing binding preference toward the H3-H4 histones (Karetsou et al, 2009), while ScNAP1 and other NAP proteins from humans are considered to be H2A-H2B histone chaperones (De Koning et al, 2007;Park et al, 2005).…”
Section: Osnapl6 Is An H3/h4 Histone Chaperonementioning
confidence: 99%
See 3 more Smart Citations